2014
DOI: 10.1039/c4tb00344f
|View full text |Cite
|
Sign up to set email alerts
|

Emerging nanostructured materials for musculoskeletal tissue engineering

Abstract: This review summarizes the recent developments in the preparation and applications of nanostructured materials for musculoskeletal tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 324 publications
(356 reference statements)
0
47
0
Order By: Relevance
“…nanostructure materials, 14 which can be further modied using various dopants with the aim of changing their surface properties. Among such dopant substances, synthetic polyanions have been observed to exhibit interesting biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…nanostructure materials, 14 which can be further modied using various dopants with the aim of changing their surface properties. Among such dopant substances, synthetic polyanions have been observed to exhibit interesting biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Classes of nanomaterials used in musculoskeletal bioengineering include natural polymers, synthetic polymers, metallic materials, inorganic materials, and nanocomposite materials [62]. The biocompatible natural polymers chitin and chitosan, derived from the crustacean exoskeleton, are of interest as a scaffold in tissue engineering these structures, and they share structural similarity to glycosaminoglycans, a key component of bone ECM [63,64].…”
Section: Bone Cartilage and Soft Tissuementioning
confidence: 99%
“…Xian and Ming [9] reported that glucose oxidase is effective in electron transfer process of enzyme adsorbed to sphere-nanostructured conductive polymer=metal oxide composite. The complexes having reduction=oxidation are efficient electron transfer mediators between the active center of glucose oxidase [10,11].…”
Section: Introductionmentioning
confidence: 99%